SINERGI AJARAN ISLAM DAN KEARIFAN LOKAL: MEMBANGUN HARMONI SOSIAL DAN KETAHANAN BUDAYA DI MASYARAKAT PLURAL - Deby Ansori; Elsa Imannia Natasya; Eka Dian Karini; Deko Rio Putra; Arini Julia (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the collaboration between Islamic principles and local wisdom in creating social harmony and cultural resilience in diverse communities, with particular attention to the practice of tahlilan in Bengkulu City. This research applies a qualitative approach through library research with descriptive-analytical and conceptual analysis. The results show that tahlilan is a blend of Islamic values and local culture that serves as a religious ritual and a means of social interaction that strengthens solidarity, cooperation, and cohesion within the community. This practice demonstrates flexible and balanced religiosity through the concepts of ‘urf and maqaṣid al-shari‘ah. However, there are obstacles related to low participation among young people and differences in perspectives between Islamic groups such as Nahdlatul Ulama and Muhammadiyah. Furthermore, there is a tendency to reform tahlilan toward a more practical, flexible form that focuses on social values. Therefore, tahlilan plays an important role in creating social harmony and strengthening cultural resilience, provided it can adapt to changes in modern society.